Advising and belonging among undergraduate women in engineering: a narrative approach - Adams-Wright, Gayla Anne (My University, 2024)
Higher education has long recognized women’s numerous challenges in undergraduate engineering programs. Several factors contribute to this lack of belonging, including a lack of diversity among student populations, microaggressions, prejudices, and traditions still rooted in male customs. An overlooked factor that may help foster a sense of belonging is undergraduate women’s conversations with academic advisors. Other studies have demonstrated that these conversations can contribute to a sense of belonging for underrepresented student groups. Faculty academic advisors, primary role advisors, and peer advisors are crucial in helping students connect with their educational, career, and life goals. This qualitative study focused on the following research question: To what extent do conversations with academic advisors contribute to a sense of belonging among undergraduate women in engineering? Using narrative inquiry to examine the stories women shared about their academic advising experiences, three themes emerged from the findings and underscore how these conversations contributed to feelings of belonging among undergraduate women in engineering. The first theme involves conversations with academic advisors who provide personalized support and guidance. The second theme revolves around conversations with academic advisors who offer encouragement during challenging experiences. The third and final theme concerns participation and engagement in conversations with peer advisors. This study highlights the positive impact that academic advising can have in fostering a sense of belonging among this population.
Keywords: Academic advising; Sense of belonging; Engineering education; Women